2014
DOI: 10.1002/esp.3645
|View full text |Cite
|
Sign up to set email alerts
|

Peatland restoration: controls on sediment production and reductions in carbon and pollutant export

Abstract: Peatlands are an important store of soil carbon, and play a vital role in global carbon cycling, and when located in close proximity to urban and industrial areas, can also act as sinks of atmospherically deposited heavy metals. Large areas of the UK's blanket peat are significantly degraded and actively eroding which negatively impacts carbon and pollutant storage. The restoration of eroding UK peatlands is a major conservation concern, and over the last decade measures have been taken to try to control erosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 96 publications
1
24
0
Order By: Relevance
“…POC fluxes were spatially and temporally variable, but high concentrations generally coincided with low or flows so did not contribute substantively to export. In areas of active peat erosion, there is strong evidence that POC export can be reduced by restoring hydrological function and vegetation cover (Shuttleworth, Evans, Hutchinson, & Rothwell, ; Worrall et al, ). However, no ditches were observed to be actively eroding at the start of our study, and although weir pools construction could have triggered a flush of POC release, this was not evident in the data.…”
Section: Discussionmentioning
confidence: 99%
“…POC fluxes were spatially and temporally variable, but high concentrations generally coincided with low or flows so did not contribute substantively to export. In areas of active peat erosion, there is strong evidence that POC export can be reduced by restoring hydrological function and vegetation cover (Shuttleworth, Evans, Hutchinson, & Rothwell, ; Worrall et al, ). However, no ditches were observed to be actively eroding at the start of our study, and although weir pools construction could have triggered a flush of POC release, this was not evident in the data.…”
Section: Discussionmentioning
confidence: 99%
“…However, at least one POM sample did show signs of that POM included vegetation, which is readily explained if a component of runoff in a peat catchment comes across the soil surface and entrains litter material. Shuttleworth et al [] have shown that the relative contribution of surface and gully wall peat to POM depends on the level of vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…Varying degrees of degradation including vegetation loss, widespread gullying, high sediment and DOC losses, etc. Rothwell et al, 2008a;Allott et al, 2009;Shuttleworth et al, 2014), have been reported in the headwaters of the Kinder plateau. Approximately 22% of the Kinder plateau (United Utilities, 2011) and~13% (52 ha) of the Kinder River catchment is bare and eroding peat.…”
Section: Study Areamentioning
confidence: 93%